Changing times: A changing public sector may require changes to public management education programmes. Issue 1 (March 2017) - Oldfield, Chrissie
It is becoming apparent that the environment in which Executive Masters in Public Administration programmes operate has changed dramatically in the wake of economic crisis and subsequent cuts in public spending. Changes in the funding of public sector organisations has been compounded by a broader "crisis" in the wider public sector which has seen job losses, resources pressures, and the questioning of who delivers public services. Despite arguing for the need for public management education in the face of adversity and austerity, the reality is that the demand for traditional university based courses is falling and despite the proven success of XMPA courses, public sector employers are just not funding or releasing their staff in the way that they did to attend these courses. Arguably, they may have justifiable "business" arguments such as loss of funding and staff and increasing demands on resources, ironically some of the senior managers who are saying no to their staff are the very ones who benefitted from more generous employer support themselves. However what this means for the development and continuance of public management programmes is that public management educators have to seriously think how to continue to develop and sustain XMPA programmes and show that they are not a burden to the organization and the sector but are of great value and benefit. This paper argues for the need for public management courses, and in particular XMPAs, during a period of questioning and uncertainty in a changing public sector. It suggests some of the changes to courses and course delivery that are needed and uses the example of the XMPA, public management education programme at London South Bank University. Such suggestions include: Delivering "Bite size XMPA", portfolio of course accumulation, a Ladders and Bridges Framework, and Continuing Professional Development (CPD). Changes to course curriculum and content, a flexible approach to course timing and delivering courses off site to organizations. Further developing Learning Communities to respond to specific workplace managerial challenges, creating a safe learning environment and developing case studies from students own professional and practical experiences. The aim of this paper is to consider ways in which public management educators can continue to provide relevant courses and skills and argues that despite the cuts in the public sector and the deprioritization of education and training, Executive Masters in Public Administration (XMPA) are much needed to enable managers to deal effectively with the managerial challenges and dilemmas in service provision, not least citizen's expectations and demands for improved services at lower cost, brought about as a consequence of the fiscal crisis and resulting public service cuts. The emphasis is on external training in the form of post graduate academic degrees and CPD (which are outside mandatory clinical and essential professional minimum training requirements), and specifically XMPA programmes.